2021
DOI: 10.1055/a-1665-9220
|View full text |Cite
|
Sign up to set email alerts
|

Red-Light-Induced N,N′-Dipropyl-1,13-dimethoxyquinacridinium-Catalyzed [3+2] Cycloaddition of Cyclopropylamines with Alkenes or Alkynes

Abstract: A red-light-mediated [3+2] annulation of cyclopropylamines with akenes or alkynes in the presence of nPr-DMQA+ has been reported. An array of cyclopentane or cyclopentene derivatives with diverse functional groups have been obtained in moderate to excellent yields under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Thus, this effective protocol for coppercatalyzed C−N direct coupling to N-(hetero)aryl cyclopropylamines was considered in comparison to those using previously reported ligands, i.e., L1−L13. As shown in Table S2, all the ligands but L12 did not perform the model reaction under our optimized condition at most only with poor conversion of 4bromoanisole, while L12 with that of 42% (Table S2, entry 12).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Thus, this effective protocol for coppercatalyzed C−N direct coupling to N-(hetero)aryl cyclopropylamines was considered in comparison to those using previously reported ligands, i.e., L1−L13. As shown in Table S2, all the ligands but L12 did not perform the model reaction under our optimized condition at most only with poor conversion of 4bromoanisole, while L12 with that of 42% (Table S2, entry 12).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Very recently, Gianetti et al further developed an n Pr-DMQA + -catalyzed [3 + 2] cyclization of cyclopropylamines 32 with alkenes 33 or alkynes 35 under red light ( λ max = 640 nm), giving rise to cyclopentane derivatives 34 in 60–95% yields or cyclopentene derivatives 36 in 33–81% yields (Scheme 2c). 20…”
Section: Direct Red Light Photoredox Catalysismentioning
confidence: 99%
“…In follow-up works, Gianetti et al continued applying 2 in some other appealing transformations. [18][19][20] In 2021, a red light-promoted trifluoromethylation/dearomatization cascade was introduced (Scheme 2b). 18 In the presence of 2 and NaHCO 3 , the indole derivatives with different dangling nucleophiles 30 reacted smoothly with Umemoto's reagent under red light, providing CF 3 -containing 3,3-spirocyclic indolines 31 in 55-87% yields.…”
Section: Dimethoxyquinacridinium (Dmqa + )mentioning
confidence: 99%
“…2-(Phenylamino)cyclopentane-1-carbonitrile (3a). 12 Cycloadduct 3a was obtained after silica gel column chromatography (EtOAc/PE = 1:10) as a separable mixture of two diastereoisomers (trans/cis = 2, 129.5, 122.4, 118.4, 113.4, 59.4, 35.4, 33.3, 29.6, 23.6 129.5, 120.4, 118.5, 113.7, 56.9, 34.3, 31.3, 28.9, 21.3 122.2, 114.5, 59.5, 35.4, 33.3, 29.6, 23.6 129.4, 123.1, 120.2, 114.8, 56.9, 34.2, 31.4, 28.9, 21.5…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Subsequently, Zheng et al reported the first visible-light-mediated intermolecular example . Jiang et al, Waser et al, Fraile/Aleman et al, Ooi et al, Aggarwal et al, Stephenson et al, Gianetti et al, and Reiser/Verma et al reported related research work, including the catalytic asymmetric ones. ,, These provided an efficient method for the construction of 2-functionalized cyclopentylamine (Scheme ).…”
Section: Introductionmentioning
confidence: 99%